2011
DOI: 10.2337/db10-0916
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia as a Mediator of the Proinflammatory Endocrine Imbalance in the Adipose Tissue in a Murine Model of the Metabolic Syndrome

Abstract: OBJECTIVEHyperuricemia is strongly associated with obesity and metabolic syndrome and can predict visceral obesity and insulin resistance. Previously, we showed that soluble uric acid directly stimulated the redox-dependent proinflammatory signaling in adipocytes. In this study we demonstrate the role of hyperuricemia in the production of key adipokines.RESEARCH DESIGN AND METHODSWe used mouse 3T3-L1 adipocytes, human primary adipocytes, and a mouse model of metabolic syndrome and hyperuricemia.RESULTSUric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
344
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(358 citation statements)
references
References 55 publications
6
344
4
4
Order By: Relevance
“…43 It is therefore clear that adiponectin is, overall, a potently renoprotective protein. The increased levels observed in CKD may be the result of metabolic changes in adipose tissue 44,45 and probably represent a compensatory upregulation over the course of CKD, without which CKD could take a more rapid negative outcome. The aforementioned conclusions are based on our past in vivo work with the ATTAC cassette in which cell-specific apoptosis was unambiguously demonstrated in wild-type, adiponectin KO, and adiponectin Tg backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…43 It is therefore clear that adiponectin is, overall, a potently renoprotective protein. The increased levels observed in CKD may be the result of metabolic changes in adipose tissue 44,45 and probably represent a compensatory upregulation over the course of CKD, without which CKD could take a more rapid negative outcome. The aforementioned conclusions are based on our past in vivo work with the ATTAC cassette in which cell-specific apoptosis was unambiguously demonstrated in wild-type, adiponectin KO, and adiponectin Tg backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid has been shown to contribute to lipoprotein oxidation and inflammation (11,18). Lanaspa et al (10) provided the first direct evidence that uric acid stimulated fat synthesis in the hepatocytes and in the pound mouse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lowering uric acid in obese mice decreased macrophage infiltration in the adipose tissue and reduced insulin resistance. Hyperuricemia may be partially responsible for the inflammation in the adipose tissue (11). A recent study demonstrated that uric acid crystals induced pro-inflammatory effects (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia, which is strongly associated with obesity and MetS and nephropathy can predict visceral obesity and insulin resistance, might be partially responsible for the pro-inflammatory endocrine imbalance in the adipose tissue, which is an underlying mechanism of the lowgrade inflammation and insulin resistance in subjects with the MetS [60][61][62][63][64][65]. Gout is a common metabolic disorder, involving the liver, kidney, and joints; it is met more often in men, and is characterized by the deposition of reversible monosodium urate (MSU) crystals and occurs as a consequence of hyperuricemia which induces inflammatory arthritis and nephropathy.…”
Section: Mets Hyperuricemia and Nephropathymentioning
confidence: 99%